ANALISIS PERBEDAAN PRINSIP PRODUK PENGHIMPUNAN DANA (FUNDING) PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL - Septi Dwi Wulandari; Nabilah Az-zahra; Simamora Desi Anna Sari; Muhammad Rifai; Muhammad Syahwildan (Kajian Ekonomi dan Akuntansi Terapan, 2024)
The bank is an official state institution in the financial sector that has the task of withdrawing and disbursing public money. Banks are one type of trusted institution among the surrounding community. Banks that have a non-trivial task make the bank also registered in the law for its security. There are many banks in Indonesia, one of which is BSI. BSI is the only bank that applies sharia principles based on the Koran and hadith. The existence of these principles makes Islamic banks not carelessly choose transactions or cooperation with other parties or customers. Uniquely, Islamic banks also use a profit sharing system as their ratio. Whereas conventional banks use the deposit interest system as their ratio. That is why researchers are interested in conducting research on the difference between the principles of Islamic banks and conventional banks in fundraising products (funding). There are three types of fundraising products in both Islamic and conventional banks, namely checking accounts, savings accounts and time deposit accounts. The difference is that Islamic banks use wadi'ah contracts and mudharabah contracts. This study aims to introduce to all people that Islamic banks have their own uniqueness and characteristics. Therefore, it is necessary to explain the contracts involved in Islamic banking. In this study, researchers used qualitative techniques. There are two data sources: Primary and secondary data sources. The researchers conducted direct interviews with informants based on primary data.